Prevalence of Operated Persons with Senile Cataracts in Heterogeneous Biotechnogenic Territories - N. V. Tyunina; E. V. Gromakina; G. G. Basova; V. G. Moses (Oftalʹmologiâ)
Purpose of the study: to evaluate the influence of the level of anthropogenic load on the frequency of surgical treatment and age status of people with senile cataracts living in various territories of the Kemerovo region — Kuzbass.Materials and methods. From 2015 to 2019, 228 372 patients from 7 cities and regions with a high level of technogenic load and from 6 cities with a low level of technogenic load were operated on for age-related cataracts in a 24-hour hospital stay.Results. The absolute number of operated persons was greater in territories with a high level of technogenic load compared to a low level of technogenic load (187 876 versus 40496) and on average exceeded 4.6 times annually (37 575 versus 8099). The number of operated persons, taking into account the dynamics of the population due to decline and birth rates in different territories over the years, fluctuated per 10 000 population, and exceeded in territories with a high level of technogenic load by an average of 27.0 %. The average age of operated patients with cataracts differed little in populations with high and low levels of technogenic load. However, in territories with a high level of technogenic load compared to a low level of technogenic load, there were 2.5 times more operated people aged 51–60 years.Conclusions. The number of operated people with senile cataracts over a five-year period per 10 000 population averaged 176.46 in areas with a high level of technogenic load and 134.14 with a low level, with a numerical advantage over decades from 9.67 % to 45.47 %, (annual average 27.0 %). There were 2.5 times more operated patients with age-related cataracts aged 51–60 years (4.9 % versus 1.9 %) in areas with a high level of technogenic load compared to a low level, with an average age of 72.02 ± 8.32 and 71.04 ± 10.11 years, respectively.